Food security and social assistance in Sudan during armed conflict: Evidence from the first round of the Sudan Rural Household Survey (November 2023–January 2024) - Kirui, Oliver K.; Ahmed, Mosab O. M.; Siddig, Khalid; Taffesse, Alemayehu Seyoum; Abushama, Hala; Dorosh, Paul A.; Krishnaswamy, Siddharth; Monetta, Cinzia; Clough, Alice; Gualtieri, Alberto; Leaduma, Amos (International Food Policy Research Institute, 2024)
The conflict in Sudan has severely impacted the food security landscape in rural areas, with profound implications for household diets, coping strategies, and overall food insecurity levels. Data from a national rural household phone survey conducted between October 2023 and January 2024 highlights the dire food consumption patterns, the prevalence of food insecurity, and the reliance on reduced coping strategies among the rural population of Sudan. As of the end of 2023, nearly 40 percent of rural households were consuming inadequate diets, with West Kordofan, South Kordofan, North Darfur, East Darfur, and Sennar states experiencing the highest prevalence of poor food consumption (34, 33, 29 and 24 percent, respectively). The primary components of diets were cereals and oils, with nutrient-rich foods, such as meats and fruits, consumed less frequently, highlighting a critical gap in nutritional adequacy. The situation has resulted in households across Sudan resorting to a range of coping strategies to try to meet their food needs, such as buying less preferred or less expensive food (on average 4 days out of 7), limiting portion sizes, or reducing the number of daily meals. The five coping mechanisms that were examined in the analysis were found to be implemented with approximately similar frequencies across rural Sudan. However, the situation was particularly dire in West Darfur, South Kordofan, and Khartoum, the states recording the highest prevalence of consumption of inadequate diets and the highest reduced Coping Strategy Index (rCSI) scores.